I walk between the raindrops : stories - Boyle, T. Coraghessan (Ecco, an imprint of HarperCollinsPublishers, 2022)
In the title story of "Walk Between the Raindrops," a woman sits down next to a man at a bar and claims she has ESP. In "Thirteen Days," passengers on a cruise line are quarantined, to horrifying and hilarious effect. And "Hyena" begins simply: "That was the day the hyena came for him, and never mind that there were no hyenas in the South of France, and especially not in Pont-Saint-Esprit--it was there and it came for him.